Nonspecific aortoarteritis as a Cause of Aortic Dissection in a Middle Aged Man - O. V. Tsygankova; S. S. Bayramova; N. M. Akhmedzhanov (Рациональная фармакотерапия в кардиологии)
Nonspecific aortoarteritis (Takayasu's disease) is a systemic inflammatory disease characterized by granulomatous lesions of the aorta and its large branches. The article describes the clinical manifestations, methods of diagnosis and treatment of this pathology. It also describes a clinical observation that illustrates the delayed diagnosis of the disease in a 47-year-old man, where Takayasu arteritis with lesions of the root, ascending aorta, both common carotid arteries, thoracic and abdominal aorta (type V according to the angiographic classification proposed by Moriwaki R.) manifested a syncopal state, just a few days before the development of a life – threatening complication-aortic dissection of type I according to the DeBakey classification. From a clinical point of view, it is important that Takayasu's disease does not always develop in young people, women, and Asian origin, and, unfortunately, it is often very late to diagnose, although the effectiveness of therapy, including surgical correction of this disease, is entirely determined by the timeliness of its diagnosis.